The Long Gilded Age: American Capitalism and the Lessons of a New World Order - Rosenow, Michael K. (Labour / Le Travail, 2016)
The article reviews the book, "The Long Gilded Age: American Capitalism and the Lessons of a New World Order," by Leon Fink.